Tindakan Kolektif Jaringan Rakyat Miskin Kota Pada Isu Legalitas Tanah Bersengketa Di Kampung Susun Akuarium - Agraprana, Hitana Mushthafa; Prameswari, Koos Savira; Dandi, Muhammad; Romadhon, Muhammad Muzakki; Sari, Putri Ayu Indah (Indonesian Democracy Research Center, 2022)
The issue of legality is on the JRMK agenda as a fulfillment of the political campaign promise of the Governor of DKI Jakarta, Anies Baswedan in the 2017 Pilkada. Anies Baswedan promised to give legal rights to land in disputed areas. However, this promise has not been fulfilled until the end of the Anies period. The purpose of this study is to find out the main focus and issues in the advocacy of the JRMK movement in the case of land legality in Kampung Susun Akuarium, in addition, to find out the Mobilizing Structures of the JRMK Jakarta advocacy movement and how JRMK manages the resources of the movement. This study uses a qualitative method by conducting interviews and in-depth observations. The results of this study see that the main focus of JRMK in advocating is to demand that the ownership status of the flats can be owned. JRMK's effort to oversee the issue of land legality in the Kampung Susun Akuarium is to take advantage of the political contract between JRMK and Anies Baswedan. The actions taken by JRMK in raising the legality of land proved that JRMK's social activities took the opportunity to change policies. Management and organization of owned resources is an important indicator to determine the success of the Kampung Akuarium community movement. Through the process of widening relations and the number of masses, the movement does not only need to increase resources, but increase the capacity and strength of the movement to the city structure.